UPAYA GURU GEOGRAFI DALAM MENINGKATKAN HASIL BELAJAR FORMATIF MENGGUNAKAN PEMBELAJARAN TIPE SCRAMBLE PADA MATERI PENGANTAR GEOGRAFI DI KELAS X SMA NEGERI 1 MENTEBAH KABUPATEN KAPUAS HULU - Rina Rina; Rika Anggela (Geography Education Study Program, Faculty of Teacher Training and Education, 2020)
This study aims to improve learning outcomes by using Scramble type learning in Class X of SMA Negeri 1 Mentebah, Kapuas Hulu Regency. The research method is the Classroom Action Research method, which is carried out collaboratively. Samples numbered 41 students. The cycle stage consists of planning the action, implementing the action, observing the action and reflecting on the action. Data collection techniques used were measurement techniques in the form of learning outcomes, direct observation techniques in the form of observation guides, and documentary techniques in the form of photographs, lesson plans and syllabi. Data analysis using the average formula (Mean). The results of the study based on the percentage of teacher observation sheets using Scramble type learning models, in cycle 1 only reached 64% and in the second cycle the results of teacher observation sheets reached 81%. completeness is 39.02% and students who are incomplete are 60.98% with an average value of 68.41. The first cycle of students is 53.66% and the total number of students who are not complete is 46.34% with an average grade of averaging 74.76. Cycle II students who completed 80.49% and students who did not complete 19.51%, with an average value of 85.00. Based on the results of this research that the Scramble type of learning has increased 85%, and has reached the indicator of success